2019
DOI: 10.1007/s12602-019-09536-7
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Activity of Enterococcus faecium and Lactococcus lactis Isolated from Thai Fermented Sausages and Their Protective Effect Against Clostridium difficile

Abstract: Lactic acid bacteria, Enterococcus faecium and Lactococcus lactis, previously isolated from Thai fermented sausages were elucidated their probiotic properties especially in the control of Clostridium difficile 630. Both isolates survived in simulated gastric solution at pH 3 followed in simulated intestinal solution at pH 8. The presence of skimmed milk also helped the bacteria to survive through acidic and alkaline in gastrointestinal conditions. The adhesion properties of both isolates were tested using a hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 28 publications
4
14
0
Order By: Relevance
“…Similar results have been observed in the current study that the L. mucosae M6-29 and L. salivarius M2-71, with strong aggregation ability, have stronger capacity to adhere to cells than other isolates. It is supposed that aggregation factors which favorably increase H-bonding between and among cell surfaces have correlation with increased general adhesion ability (29). Our results support the hypothesis that a notable correlation was observed between aggregation and adhesion.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar results have been observed in the current study that the L. mucosae M6-29 and L. salivarius M2-71, with strong aggregation ability, have stronger capacity to adhere to cells than other isolates. It is supposed that aggregation factors which favorably increase H-bonding between and among cell surfaces have correlation with increased general adhesion ability (29). Our results support the hypothesis that a notable correlation was observed between aggregation and adhesion.…”
Section: Discussionsupporting
confidence: 87%
“…The Caco-2 cells and IPEC-J2 cells were cultivated as described by Dowdell et al (29). Briefly, the cells were plated into 24well plates.…”
Section: Adhesion Assaymentioning
confidence: 99%
“…They showed that Bifidobacterium longum and Bifidobacterium breve were able to reduce the toxic effects of the pathogen on HT-29 cell lines and rounding was prevented and F-actin microstructure and tight junctions between adjacent cells were preserved. E. faecium and L. lactis have also been shown to help protect epithelial cells from C. difficile toxins (11). Similarly, the results of our study showed that six E. faecalis may secrete antibacterial agents that reduce the cytotoxic effects of toxins of C. difficile and protect HT-29 cells.…”
Section: Discussionsupporting
confidence: 78%
“…Various antimicrobial mechanisms have been attributed to LAB probiotics. These include nutrient competition, prevention of mucosal cell adhesion, and internalization of pathogens such as C. difficile ( 9 , 11 , 12 ). Moreover, LAB strains can produce lactic acid and certain antimicrobial molecules such as hydrogen peroxide, fatty acid, and bacteriocins to exert their antimicrobial activity ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…New evidence shows that CFS from various lactic acid bacteria (LAB) cocultured with multi-resistant C. difficile can reduce the cytotoxic effects of clostridial toxins on different cell lines compared to pure C. difficile CFS. Additionally, neutralized CFS from LAB + C. difficile can reduce the level of IL-8 and tumor necrosis factor α (TNF-α), two pro-inflammatory cytokines released by intestinal epithelial cells, caused by the CFS of C. difficile [ 67 , 68 ].…”
Section: Potential Mechanisms Of Actionmentioning
confidence: 99%